Electronic structure tuning and band gap opening of nitrogen and boron doped holey graphene flake: The role of single/dual doping - Omidvar, Akbar (Materials chemistry and physics, 2017)
Opening a bandgap in graphene is one of the most important subjects in the graphene research currently, since most of the suggested applications for graphene in field-effect transistors and optoelectronic devices require the ability to adjust its bandgap. To solve this problem, a novel graphene-like nanomaterials, i.e. a nitrogenated holey graphene has been recently synthesized using a simple wet-chemical reaction (Nat. Commun. 2015, 6, 6486). Motivated by this experimental work, in the present study, the structural and electronic properties of the zero dimensional (0D) holey graphene flake are investigated using first-principles calculations. In the framework of density functional theory, we analyze the effects of number of doped atoms (nitrogen and boron) on the structure, stability, and electronic properties of the holey graphene flake. In our survey, we have explored the stability of pristine as well as doped and co-doped holey graphene flake by studding of band gap energy as well as cohesive energy, chemical hardness, hyper-hardness, electrophilicity index, and dipole moment values of the considered flakes. The present study opens the way for manipulating holey graphene and developing promising materials for applications in field-effect transistors and optoelectronic devices. [Display omitted] •Single doping holy graphene with nitrogen and boron atoms.•Bonded and separated co-doping holy graphene with nitrogen and boron atoms.•Predicting the stability of holy graphene by different electronic descriptors.